1993
DOI: 10.1073/pnas.90.17.8088
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and germ-line transmission of a null mutation at the metallothionein I and II loci in mouse.

Abstract: We report the generation of transgenic mice deficient in the metallothionein MT-I and MT-Il genes. The mutations were introduced into embryonic stem cells by homologous recombination. Chimeric mice resulting from the targeted embryonic stem cells transmitted the disrupted alleles through their germ line. Homozygous animals were born alive and appeared phenotypically normal and fertile. Absence of MT proteins was confirmed by direct measurement in liver extracts. Challenging the mutant animals with moderate lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
213
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(220 citation statements)
references
References 27 publications
5
213
1
1
Order By: Relevance
“…MT-null mice whose MT-I and MT-II genes had null mutations and wild-type mice were kindly provided by Dr. A. Choo (Murdoch Institute for Research into Birth Defects, Royal Children's Hospital, Parkville, Australia) (Michalska and Choo, 1993). Both kinds of mice were originally from a mixed genetic background of OLA129 and C57BL6 strains.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…MT-null mice whose MT-I and MT-II genes had null mutations and wild-type mice were kindly provided by Dr. A. Choo (Murdoch Institute for Research into Birth Defects, Royal Children's Hospital, Parkville, Australia) (Michalska and Choo, 1993). Both kinds of mice were originally from a mixed genetic background of OLA129 and C57BL6 strains.…”
Section: Animalsmentioning
confidence: 99%
“…MT-III and MT-IV isoforms exist in neural tissue and squamous epithelium, respectively (Masters et al, 1994b;Quaife et al, 1994). Recently, MT-null transgenic mice that are deficient in MT-I and MT-II were produced by the gene-targeting technique (Masters et al, 1994a;Michalska and Choo, 1993). Several studies have shown that MT-null mice have an increased sensitivity to oxidative stress induced by paraquat (Sato et al, 1996), ultraviolet (Hanada et al, 1998), or acetaminophen (Rofe et al, 1998;Zhang et al, 1999;Liu et al, 1999).…”
mentioning
confidence: 99%
“…Although transgenic mice lacking functional MT genes have been shown to grow and reproduce normally (Michalska & Choo, 1993;Masters et al, 1994), they, however, display increased sensitivity to chemical stress, compared to wild-type mice (Lazo et al. 1995;Philcox et al, 1995;Rofe et al, 1996).…”
mentioning
confidence: 99%
“…7 Nevertheless, results from 2 independent groups led to the conclusion that unexposed MT-1/2 knockout mice are viable and reproduce normally. 8,9 Although the role of MT in cisplatin susceptibility of normal kidney cells appears to be clear, the situation remains inconclusive for tumor cells. A large number of experiments have shown MT involvement in anti-cancer drug resistance, especially against platinum compounds.…”
mentioning
confidence: 99%